(untitled) (Plant Bulletin, 2025)
Ten genotypes of chickpeas (Cicer arietinum L.) were examined in this study for their ability to resist drought in both normal and water stress environments through the evaluation of numerous morpho-physiological characteristics at various growth stages. Genotypes were assessed for characteristics such as plant length, root length, chlorophyll index, number of seeds per plant, pod production, and seed weight under both normal and drought conditions during field experiments at Muhammad Nawaz Sharif University of Agriculture, Multan. Factorial Randomized Complete Block Design (RCBD) with three replications were used in this experiment. The analysis of variance showed highly significant (p<0.01) genotypic variations across all traits. Biplot analyses explained 70.6% of the total variation, with Dim-1 representing major yield traits and Dim-2 reflecting plant and root growth, enabling clear differentiation of genotypes. NOOR-2009, TGN-2213 and TGN-2240 consistently aligned with favorable yield-related Traits arrows and showed improved root development, pod production and seed set under stress. Among these, NOOR-2009 exhibited the greatest drought resilience, with only an 11% yield reduction and performed best under normal and drought conditions. This study highlights the importance of selection of drought-tolerant genotypes for breeding programs to enhance climate resilience and to safeguard food security.